Interpret: Apply or create right? Analysis from the perspective of private law - Mantilla Espinosa, Fabricio (2018)
The task undertaken in this essay is to analyze the interpretation of the legal norms in order to be used in the solution of the cases brought before the judge. However, many of the theoretical constructs elaborated to explain it not only seem to be completely removed from the activity that the judges perform in the day to day of the exercise of their works, but, in addition, they are elaborated in an abstruse and vaporous language that evil could be compared with the practice of law. The objective of this essay is to try to specify clearly and concisely the parameters established by private law for the judicial interpretation of the rules, highlighting the broad powers available to the judges, but without leaving aside the limits that must respect.